Microglia Activation in Basal Ganglia Is a Late Event in Huntington Disease Pathophysiology. Issue 3 (May 2021) - Rocha, Natalia P.; Charron, Odelin; Latham, Leigh B.; Colpo, Gabriela D.; Zanotti-Fregonara, Paolo; Yu, Meixiang; Freeman, Leorah; Furr Stimming, Erin; Teixeira, Antonio L.
Abstract : Objective: To define the role played by microglia in different stages of Huntington disease (HD), we used the TSPO radioligand [11C]-ER176 and PET to evaluate microglial activation in relation to neurodegeneration and in relation to the clinical features seen at premanifest and manifest stages of the disease. Methods: This is a cross-sectional study in which 18 subjects (6 controls, 6 premanifest, and 6 manifest HD gene carriers) underwent a [11C]-ER176 PET scan and an MRI for anatomic localization. Segmentation of regions of interest (ROIs) was performed, and group differences in [11C]-ER176 binding (used to evaluate the extent of microglial activation) were assessed by the standardized uptake value ratio (SUVR). Microglial activation was correlated with ROIs volumes, disease burden, and the scores obtained in the clinical scales. As an exploratory aim, we evaluated the dynamic functions of microglia in vitro, by using induced microglia-like (iMG) cells from peripheral blood monocytes. Results: Individuals with manifest HD present higher [11C]-ER176 SUVR in both globi pallidi and putamina in comparison with controls. No differences were observed when we compared premanifest HD with controls or with manifest HD. We also found a significant correlation between increased microglial activation and cumulative disease burden, and with reduced volumes. iMG from controls, premanifest HD, and manifest HD patients showed similar phagocytic capacity. Conclusions: Altogether, our data demonstrate that microglial activation is involved in HD pathophysiology and is associated with disease progression.